Innovative Marketing Tools: A Case Study of IDFC Mutual Fund - Pooja Sharma; Manisha Gupta (STIE Malangkucecwara, 2016)
The present study is based on various innovative physical tools, videos and movies “One Idiot” and “Bachat Nivesh Badhat” made by IDPC (Infrastructure Development Finance Company) mutual fund company. IDFC has made various tools but in this study taken only Pyramid puzzle, T-puzzle and newspaper tool. Marketing tools made by IDFC mutual funds are game changer for a mutual fund industry. The purpose of the study is to study the effect of IDFC movies “One Idiot” and “Bachat Nivesh Badhat” on customer, effect of various physical tools made by IDFC on customer to understand their needs and effect of game changer tools of IDFC by creating more happy mutual fund investors. The study is based on respondents of 200 investors of Jalandhar and Hoshiarpur. The study concludes that with the help of tools and movies made by IDFC it had brought ease in the customers to understand the concept and make a wiser decision rather than just depending on the thorough concept. Thus, marketing strategies plays an important role in the overall market development and this will expand the investors’ base of mutual fund industry.